2017
DOI: 10.5812/jjm.61522
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-Spectrum β-Lactamases and Antibiotic Resistance Patterns in Acinetobacter baumannii Isolated from Clinical Samples in Kermanshah, Iran

Abstract: Background: Acinetobacter is an opportunistic bacterial pathogen with intrinsic and acquired resistance to many antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In the current study, 62.6% of A. baumannii isolates were ESBL producers. Our results were consistent with two other studies in Iran in 2013 in Tabriz and in 2017 in Kermanshah on A. baumannii isolates which showed that 70% and 53.8% of the isolates produced ESBL, respectively ( 32 , 34 ). However, we found a higher prevalence of ESBL-producing A. baumannii compared with other studies in Iran in Hamedan (7%) and Tehran (16%) ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, 62.6% of A. baumannii isolates were ESBL producers. Our results were consistent with two other studies in Iran in 2013 in Tabriz and in 2017 in Kermanshah on A. baumannii isolates which showed that 70% and 53.8% of the isolates produced ESBL, respectively ( 32 , 34 ). However, we found a higher prevalence of ESBL-producing A. baumannii compared with other studies in Iran in Hamedan (7%) and Tehran (16%) ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 93%
“…In one study in Iran, the prevalence of blaTEM and blaCTX genes was 52.1% and 43.4%, respectively, in ESBL-producing A. baumannii isolates (36). Two other studies also reported the presence of blaCTX-M and blaTEM genes in clinical isolated of ESBL-producing A. baumannii isolates (34,37). In 2019, 42% of A. baumannii strains isolated from patients admitted to hospitals in Tehran were positive for the blaTEM gene and negative for the presence of the blaSHV gene (33).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of class-D OXA carbapenemase genes has been linked to the vigorous biofilm growth caused by A. baumannii (4). Class I integrons are found across the MDR A. baumannii strain population in high numbers (5).…”
Section: Introductionmentioning
confidence: 99%
“…Different species of this genus can cause various nosocomial infections, commonly among patients in intensive care units (ICUs) and highdependency units (HDUs) [3]. Acinetobacter baumannii is more prevalent than other strains of genus Acinetobacter, and it is the most common cause of bacterium-induced infections [4]. Ventilatorassociated pneumonia (VAP), septicemia, secondary meningitis, endocarditis, infections of the skin, soft tissues, urinary tract, and wound infection can be caused by bacteria A. baumannii bacteria [5].…”
Section: Introductionmentioning
confidence: 99%
“…To treatment of A. baumannii infections, various antibiotics, including β-lactams, uoroquinolones, and aminoglycosides, are used. Today, many studies have shown that antibiotic resistance in the A. baumannii isolates is extremely increasing [3,4,6,7]. Inappropriate and indiscriminate use of available antibiotics, high ability of natural genetic transformation in A. baumannii bacteria and its potential for widespread dissemination are most important factors contributed to the resistance of this pathogen to the various antimicrobial agents [8,9].…”
Section: Introductionmentioning
confidence: 99%